2022
DOI: 10.2169/internalmedicine.8034-21
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Outcomes of Small-bowel Angioectasia in Systemic Sclerosis Patients: A Retrospective Observational Study

Abstract: Objective Systemic sclerosis (SSc) is defined as an autoimmune disease presenting with fibrosis of various organs and vascular endothelial damage. Vascular lesions, including small-bowel angioectasias, are also frequently detected in SSc patients. Polidocanol injection (PDI) is a safe and effective hemostatic treatment for gastrointestinal bleeding. We evaluated the outcomes of PDI for small-bowel angioectasia in SSc patients. Methods We retrospectively evaluated 65 consecutive SSc patients (61 women; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A study involving 65 SSc patients suggested polidocanol injections as a useful and possible treatment for SScrelated small-bowel angioectasia (99). Hii et al reported a significant improvement of heartburn in SSc patients with GERD at 3 months, and at 1 and 3 years after partial fundoplication (100).…”
Section: Gastrointestinal Involvementmentioning
confidence: 99%
“…A study involving 65 SSc patients suggested polidocanol injections as a useful and possible treatment for SScrelated small-bowel angioectasia (99). Hii et al reported a significant improvement of heartburn in SSc patients with GERD at 3 months, and at 1 and 3 years after partial fundoplication (100).…”
Section: Gastrointestinal Involvementmentioning
confidence: 99%